Teleteaching in paediatric rheumatology: an Asia Pacific League of Associations for Rheumatology experience - Sumaira Farman; Muhammad Kamil Hussain Raja; Elizabeth Y. Ang; Swee-Ping Tang; Kosar Asna Ashari; Saira Elaine Anwer Khan (Exploration of Musculoskeletal Diseases, 2024)
Aim: To evaluate the reach and potential effectiveness of teleteaching of health providers in paediatric rheumatology by observing the pattern of sessions, attendance, and attendees’ feedback in paediatric rheumatology teleteaching sessions across the Asia Pacific region. These were conducted by the Asia Pacific League of Associations for Rheumatology (APLAR) Paediatric Rheumatology Special Interest Group (Paeds Rheum SIG) as an APLAR academy activity. Methods: A retrospective, descriptive analysis of electronic records of synchronous telehealth sessions held between July 2021 to July 2023. These followed three formats: case-based webinars, single topic modular online course, and a hybrid one-day short course. The topics of sessions, attendees’ registration details, specifically primary area of practice/specialty, geographic location, and their satisfaction as per feedback forms were noted. Results: Case-based webinars had an average attendance of 200 per webinar: majority adult rheumatologists, paediatric rheumatologists (PRs), or paediatricians. The modular course consisted of nine sessions with an average of 63 participants per session. Specialties comprised PRs, adult rheumatologists with immunologists, and general paediatricians. The one-day hybrid course had over 600 attendees. Attendees were adult rheumatologists, general physicians, paediatricians, and PRs. Although the majority (79.3%) of attendees from these sessions were from APLAR member nation organisations (MNOs), a significant percentage (20.7%) were from non-APLAR MNOs and even non-Asia Pacific regions. The attendees’ feedback for all three formats showed a high level of satisfaction with case-based webinars being most favoured. Conclusions: Teleteaching in paediatric rheumatology has the potential to fulfill the dire need for improved expertise of health professionals managing children with rheumatic diseases. Case-based, interactive sessions of shorter duration and a blended hybrid format may garner the most attendance and best learning outcomes.